Hate Crime Legislation Reconsidered. (October 2016) - Baron, Marcia
Abstract: In "Is Penalty Enhancement a Sound Idea?" Claudia Card calls into question hate crime legislation, querying whether hatred makes a crime worse, whether hatred of the sort pertinent to hate crimes is worse than a more personal hatred, and whether the message sent by hate crime legislation is the intended message. This essay questions her assumption that penalty enhancement for hate crimes is warranted only if the crimes are worse than otherwise similar crimes that do not count as hate crimes. Instead, it may be the case that it is the proper business of the state to take a particular interest in such crimes, in part because they enact not just any hatred but civic hatred. And if hate crimes are understood as enacting civic hatred, hate crime legislation can indeed serve to counter a message that very much needs to be countered.